Kajian Sosiologi Sastra Dalam Novel Rapijali 1: Mencari Karya Dee Lestari - Aryani, Yeni; Missriani, Missriani; Effendi, Darwin (Institut Teknologi Pendidikan Indonesia, 2022)
Sociology of literature studies humans as social beings seen from aspects of everyday people's lives. This research describes the following things. 1) Social Process 2) Social Problems 3) Social Change contained in the novel Rapijali 1: Searching for the work of Dee Lestari. The method used by the researcher is a qualitative descriptive method. Qualitative descriptive method solves the problem being studied by describing or describing the object of research based on visible facts. The data collected in the form of words or paragraphs contained in the novel Rapijali 1: Searching by Dee Lestari. The results of the study found that there was a sociology of literature contained in this study in the form of social processes which are social interactions related to cooperation, such as mutual assistance and mutual assistance activities to achieve the desired common goals. then there is competition, contention or contention, and accommodation. There are also social problems including crime, poverty, and environmental problems related to the environment in which they live and environmental problems related to humans themselves. The social changes contained in the novel are in the form of evolutionary changes and revolutionary changes, as well as planned and unplanned changes. Based on the results of the analysis and discussion above, it can be concluded that the novel Rapjali 1: Searching by Dee Lestari is an interesting novel to study. In this novel there are many life lessons that can be applied in everyday life.